Penerapan Pendekatan Humanistik Untuk Meningkatkan Hasil Belajar Pendidikan Agama Hindu di Prodi PSABB STAH Negeri Mpu Kuturan Singaraja - I Nengah Juliawan (Pramana: Jurnal Hasil Penelitian, 2022)
Observing the problem of achieving minimum mastery requirements for learning, it is essentially controlled by the learning process, not only by good input. In this case, a teacher must be able to design learning as accurately as possible based on the capacity of students. Teachers can use a humanistic approach to help students learn more effectively. As in this study, the Humanistic Approach can help students of PSABB STAH Study Program Kuturan Singaraja Negeri in improving their learning outcomes. The results of this study are as follows, student learning outcomes also experienced a significant increase in cycle I, the average student learning outcomes were 68, increased to 78 in cycle II and in cycle III to 89. While seen from classical completeness there was also an increase from 45% in the first cycle, to 63% in the second cycle and increased to 92% in the third cycle